An Artistic Experience in Residency Interview with Ivo Alexandre (Revista Apotheke, 2025)
Interview conducted with the Portuguese artist and student Ivo Alexandre (Fbaul), during one of his visits to Fabrício Rodrigues Garcia’s studio in the city of Garopaba, during an artistic residency held in 2024. The interview unfolded from John Dewey’s concept of experience, related to the experiences lived by the artist during his artistic residency and his painting process during the three months he spent in Brazil. During this period, he lived in the city of Florianópolis, visiting and staying for ten days in the city of Garopaba, where the artist produced and immersed himself in painting, producing works that were later exhibited. During this journey, the artist exposes the singularities he experienced, which allowed him to produce works that directly dialogue with his creative imagination during a long-term residency.
Keywords: John Dewey; Ivo Alexandre; Experience; Artistic Residency; Painting